A descriptive study on the presence of adulterants in #3 repacked alginate impression materials - Arriola, Ma. Cecille; Urruiquia, Alex.; Segarra, Armin (Adviser).; Estaniel, Cynthia (Adviser).
6 alginate impression materials, 3 brands of original packs and one repacked alginate for each brand were analyzed under a scanning electron microscope to determine if there are adulterants present in the elemental compositions of the original packs compared to the repacked materials but there were no significant findings as to whether there are adulterants present in the materials.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental impression materials